(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction: Quality in laboratory medicine have a significant role in ensuring the adequate and complete total testing process. Clinical laboratory and testing process is an integral part of modern medicine as it has a direct effect on the patient. As per the requirement of certification or accreditation bodies, different laboratories use different ways of developing quality indicators (QI), which helps to monitor, progress and maintain the quality of the laboratory services. Materials and Methods: A cross sectional retrospective study carried out in the Hematology Laboratory of a tertiary care hospital. Data of pre-analytical quality indicators was collected for months from August 2015 to January 2016. Pre-analytical quality indicators analysed for sample collections were clotted sample, hemolyzed sample, incompletely filled form, wrong labelled sample, insufficient sample volume and patient waiting for sample collection after registration in the laboratory- turnaround time (TAT). Turn around time for patient waiting for sample collection is 15 minutes from the registration of the request form. Results: The overall sample received during the six months was 2,03,337 among these pre-analytical errors found in 1067. The highest rate indicators were clotted sample 589 (0.28%), followed by insufficient sample volume 376(0.18), incompletely filled form and wrongly labelled sample 67(0.03%), Hemolyzed sample 35(0.017%). 94.49 % of the patient waiting time for the sample collection from registration was within the Turnaround time (TAT). Conclusion: The development of a quality indicator for clinical laboratory medicine helps to improve quality in processing and testing of samples. Quality indicator plays a vital role in continuous improvement activities of clinical practice, which are aiming to deliver quality result and reducing the errors. Bangladesh Journal of Medical Science Vol.20(3) 2021 p.525-529